Identity Contamination and the Symptoms of Subalternity in Khadra’s The Swallows of Kabul - Lahcen SAHOUANE; Boudjemaa BELGUELIEL (UNIVERSITÉ MOHAMED BOUDIAF - M’SILA, 2024)
The present dissertation analyses how the harsh socio-political environment affects and damages the identities of people. Yasmina Khadra's novel, The Swallows of Kabul, is the corpus of this study, concentrating first on the central issue: how the characters’ identities are shaped by the oppressive setting in Afghanistan, highlighting the symptoms of identity contamination and subalternity prevalent throughout the narrative. The research analyses the novel’s narrative and characters using essential concepts from postcolonial studies. The findings reveal that the oppressive power structures and social hierarchies create identity loss and mental stress, reflecting Subalternity, which concentrates on the impact of marginalization and cultural oppression. The research concludes that the novel presents a deep understanding of identity-power relations, giving insights into the struggles of voiceless and marginalized individuals in a postcolonial world, echoing the theories of Gayatri Spivak.
Keywords: Yasmina Khadra; Identity; Subalternity; Afghanistan; Oppression; Marginalization.